Chapter 10: Bioactive Glass Particulate-incorporated Polymer Composites - Naseri,S; Boccaccini,AR; Nazhat,SN (2017)
Bioactive glasses can potentially be used in combination with polymers in order to create a new complex of enhanced bioactivity, biocompatibility, and mechanical and degradation properties for biomedical applications. There are various processing routes to fabricate particulate bioactive glass fillers composites (dense or porous). Each fabrication route has its own advantages and disadvantages, and the best fabrication route is determined depending on the materials used and the desired final application. In this chapter, the main particulate bioactive glass-incorporated polymer composite fabrication techniques are presented, along with their associated pros and cons. Additionally, the properties of the various composites for tissue engineering and biomedical applications are discussed.